Application of champedak mannose-binding lectin in the glycoproteomic profiling of serum samples unmasks reduced expression of alpha-2 macroglobulin and complement factor B in patients with nasopharyngeal carcinoma - Seriramalu, R.; Pang, W.W.; Jayapalan, J.J.; Mohamed, E.; Abdul-Rahman, P.S.; Bustam, A.Z.; Khoo, A.S.B.; Hashim, Onn Haji (2010)
The use of lectin affinity chromatography prior to 2-DE separation forms an alternative method to unmask the expression of targeted glycoproteins of lower abundance in serum samples. Reduced expression of alpha-2 macroglobulin (AMG) and complement factor B (CFB) was detected in sera of patients with nasopharyngeal carcinoma (NPC) when pooled serum samples of the patients and those of healthy individuals were subjected to affinity isolation using immobilized champedak mannose-binding lectin and analyzed by 2-DE and densitometry. The AMG and CFB spots were not detected in the 2-DE protein profiles when the same pooled serum samples were subjected to albumin and IgG depletion and neither were they detected when the depleted samples were analyzed by western blotting and lectin detection. Together with other acute-phase response proteins that were previously reported to be altered in expression in NPC patients, AMG and CFB may serve as useful complementary biomarkers for NPC.